The Effect of Collecting Advertisement Tax, Restaurant Tax and Parking Tax on Makassar City Original Regional Income (PAD) - Arman, Rifqah Zakiyah; Haliah; Nirwana (Lembaga Riset Ilmiah, 2024)
This research aims to examine how the collection of rec tax, restaurant tax and parking tax influences the efforts of the city of Makassar to increase its regional natural income and the impact of tax collection on efforts to increase regional natural income (PAD). This research uses advertising tax contributions, restaurant tax contributions and parking tax contributions as independent variables. Meanwhile, the dependent variable in this research is local original income. The population in this study is government officials within the Makassar City revenue service. The sample will be selected using a purposive sampling technique. The data analysis method used is multiple linear analysis. The results of the regression test show that collection of advertising tax, restaurant tax and parking tax has a positive effect on increasing local revenue in Makassar City. This means that the higher the advertising tax collected, the greater the regional income will increase.